Aberrant Brain Regional Homogeneity and Functional Connectivity in Middle-Aged T2DM Patients: A Resting-State Functional MRI Study - Liu, Daihong; Duan, Shanshan; Zhang, Jiuquan; Zhou, Chaoyang; Liang, Minglong; Yin, Xuntao; Wei, Ping; Wang, Jian (Frontiers in Human Neuroscience, 2016)
Type 2 diabetes mellitus (T2DM) has been associated with cognitive impairment. However, its neurological mechanism remains elusive. Combining regional homogeneity (ReHo) and functional connectivity (FC) analyses, the present study aimed to investigate brain functional alterations in middle-aged T2DM patients, which could provide complementary information for the neural substrates underlying T2DM-associated brain dysfunction. Twenty-five T2DM patients and 25 healthy controls were involved in neuropsychological testing and structural and resting-state functional magnetic resonance imaging data acquisition. ReHo analysis was conducted to determine the peak coordinates of brain regions with abnormal local brain activity synchronization. Then, the identified brain regions were considered as seeds, and FC between these brain regions and global voxels was computed. Finally, the potential correlations between the imaging indices and neuropsychological data were also explored. Compared with healthy controls, T2DM patients exhibited higher ReHo values in the anterior cingulate gyrus and lower ReHo in right fusiform gyrus, right precentral gyrus and right medial orbit of the superior frontal gyrus. Considering these areas as seed regions, T2DM patients displayed aberrant FC, mainly in the frontal and parietal lobes. The pattern of FC alterations in T2DM patients was characterized by decreased connectivity and positive to negative or negative to positive converted connectivity. Digital Span Test forward scores revealed significant correlations with the ReHo values of the right precentral gyrus (ρ = 0.527, p = 0.014) and FC between the right fusiform gyrus and middle temporal gyrus (ρ = -0.437, p = 0.048). Our findings suggest that T2DM patients suffer from cognitive dysfunction related to spatially local and remote brain activity synchronization impairment. The patterns of ReHo and FC alterations shed light on the mechanisms underlying T2DM-associated brain dysfunction and might serve as imaging biomarkers for diagnosis and evaluation.